Pengaruh E-Service Quality, Online Customer Rating, dan Online Customer Review terhadap Keputusan Pembelian di Aplikasi Fore Coffee Surabaya Barat - Arif Dhia Misbahuddin; Wiwik Herawati (Jurnal Riset dan Inovasi Manajemen, 2025)
The rapid development of digital technology has significantly transformed consumer behavior, making online applications the primary channel for interaction and transactions. These applications provide convenience for consumers to access various products and services quickly and efficiently. In this context, the quality of service provided, along with the rating and reviews shared online, plays a crucial role in influencing purchasing decisions. For instance, the Fore Coffee app allows consumers to leave reviews and ratings, which can influence other consumers in selecting the desired products or services. These factors are essential in increasing customers' purchase intention, as consumers tend to rely on the experiences of others as references when making decisions. This study uses a quantitative approach by distributing questionnaires to consumers of the Fore Coffee app in West Surabaya. The study aims to determine the extent to which service quality, ratings, and reviews affect consumers' purchase intentions. The data collected were then processed using SPSS version 20 to conduct validity tests, reliability tests, multiple linear regression, and t-tests. Validity and reliability tests were conducted to ensure that the instruments used in this research accurately and consistently measure the relevant variables. Multiple linear regression was used to analyze the relationship between the independent variables (service quality, ratings, and reviews) and the dependent variable (purchase intention). Meanwhile, t-tests were used to examine the significant impact of each variable on purchase intention. The findings of this study can provide valuable insights for Fore Coffee in formulating more effective marketing strategies. The results indicate that service quality, ratings, and reviews significantly influence consumers' purchase intentions. With this understanding, Fore Coffee can improve the customer experience and strengthen its competitive position in an increasingly competitive market.